Association of retinal atrophy with cortical lesions and leptomeningeal enhancement in multiple sclerosis on 7T MRI. (March 2022) - Mizell, Ryan; Chen, Hegang; Lambe, Jeffrey; Saidha, Shiv; Harrison, Daniel M
Background: Retinal atrophy in multiple sclerosis (MS) as measured by optical coherence tomography (OCT) correlates with demyelinating lesions and brain atrophy, but its relationship with cortical lesions (CLs) and meningeal inflammation is not well known. Objectives: To evaluate the relationship of retinal layer atrophy with leptomeningeal enhancement (LME) and CLs in MS as visualized on 7 Tesla (7T) magnetic resonance imaging (MRI). Methods: Forty participants with MS underwent 7T MRI of the brain and OCT. Partial correlation and mixed-effects regression evaluated relationships between MRI and OCT findings. Results: All participants had CLs and 32 (80%) participants had LME on post-contrast MRI. Ganglion cell/inner plexiform layer (GCIPL) thickness correlated with total CL volume ( r =−0.45, p < 0.01). Participants with LME at baseline had thinner macular retinal nerve fiber layer (mRNFL; p = 0.01) and GCIPL ( p < 0.01). Atrophy in various retinal layers was faster in those with certain patterns of LME. For example, mRNFL declined –1.113 (–1.974, –0.252) μm/year faster in those with spread/fill-pattern LME foci at baseline compared with those without ( p = 0.01). Conclusion: This study associates MRI findings of LME and cortical pathology with thinning of retinal layers as measured by OCT, suggesting a common link between meningeal inflammation, CLs, and retinal atrophy in MS.